A reversible and highly conductive adhesive: towards self-healing and recyclable flexible electronics. Issue 23 (12th May 2020) - Yan, Qiming; Zhou, Meng; Fu, Heqing
Abstract : Flexible conductive adhesives are important materials for the next generation of flexible electronic devices. Abstract : Flexible conductive adhesives are important materials for the next generation of flexible electronic devices. Herein, we prepared a reversible conductive flexible adhesive (RCFA) based on a furan-terminated four-armed polyurethane resin, urea-group-grafted multi-walled carbon nanotubes (urea- g -MWCNTs) and silver nanoparticle decorated multi-walled carbon nanotubes (Ag@MWCNTs). This adhesive has good mechanical robustness, fast self-healing capability under near-infrared (NIR) irradiation and high electrical conductivity under mechanical deformation. At the same time, the fast self-healing and the reinforced electrical conductive mechanisms of RCFA were analyzed. Mechanical tests showed that with the incorporation of 3 wt% urea- g -MWCNTs and 7 wt% Ag@MWCNTs, the ultimate strength and the break strain of RCFA can reach as high as 14.79 MPa and 603%, respectively. Owing to the reversible Diels–Alder reaction and hydrogen bonding interaction, the conductive adhesive exhibited more than 90% self-healing efficiency after 20 min of NIR irradiation. Moreover, the electrical resistivity of RCFA was about 0.15 Ω cm and can be maintained during stretching and bending processes. Finally, we explored the potential applications of the as-prepared RCFA in light emitting diode arrays and radio frequency identification. Our report may open an effective pathway to fabricate reversible conductive flexible adhesives for the next generation of flexible electronic devices.